2018
DOI: 10.1007/s00415-018-8891-y
|View full text |Cite
|
Sign up to set email alerts
|

Influences of temporal lobe epilepsy and temporal lobe resection on olfaction

Abstract: Although temporal lobe epilepsy (TLE) and resection (TLR) impact olfactory eloquent brain structures, their influences on olfaction remain enigmatic. We sought to more definitively assess the influences of TLE and TLR on olfaction using three well-validated olfactory tests and measuring  the tests' associations with the volume of numerous temporal lobe brain structures. The University of Pennsylvania Smell Identification Test and an odor detection threshold test were administered to 71 TLE patients and 71 age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Resection of piriform cortex was safe and there was no impact on neurocognitive performance in regard of extent of resection. Although the role of piriform cortex in initiation and propagation of seizures is well described in animal models, there is little evidence regarding the exact function of piriform cortex in humans 36–38 . Therefore, further research is required to correlate the extent of resection with both seizure as well as neurocognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Resection of piriform cortex was safe and there was no impact on neurocognitive performance in regard of extent of resection. Although the role of piriform cortex in initiation and propagation of seizures is well described in animal models, there is little evidence regarding the exact function of piriform cortex in humans 36–38 . Therefore, further research is required to correlate the extent of resection with both seizure as well as neurocognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of the temporal lobe is not fully understood, but auditory perception is one of its main functions. Some visual skills and language, memory, and some motor functions may depend on the temporal lobe [30,31].…”
Section: And Mathematical Performancementioning
confidence: 99%
“…Although the study of olfactory performance in epilepsy is limited, previous studies have noted that profound interictal olfactory dysfunction is present in patients with temporal lobe epilepsy ipsilateral to the seizure focus. 13,[15][16][17][22][23][24][25]30 In their pioneering study, Savic et al tested odor discrimination ability in mTLE patients and found that odor discrimination performance was more impaired in the nostril that was ipsilateral to the epileptogenic region. 24 Patients with mTLE made more discrimination errors compared to patients with neocortical seizures and matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Given emerging evidence that 40%‐60% of patients do not achieve seizure freedom with MRgLiTT, 10,11 identification of presurgical factors that predict postoperative seizure control is important to identify appropriate candidates for MRgLiTT. Previous studies have observed interictal olfactory dysfunction in TLE, with variable impairment on observed measures of odor detection threshold, odor identification, and odor discrimination 12–16 . A recent investigation by Espinosa‐Jovel et al found that patients with mTLE showed greater baseline olfactory dysfunction than patients with extrahippocampal focal epilepsy and healthy controls 17 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation